Parental Perspectives Regarding the Return of Genomic Findings in NeuroDevelopmental Disorders – A South African Study - Diedericks, Angelique (Department of Clinical Laboratory Sciences, 2020)
Introduction: There is a lack of policies and research regarding the disclosure of results in genomic research, especially in South Africa. Challenges remain regarding the disclosure of genomic research results to research participants and their families, which may partly be addressed by considering parental and participants' preferences. This study serves as a sub-study to the NeuroDev study which is performing genotyping and exome sequencing on children with NeuroDevelopmental disorders in the Western Cape; and will investigate a feedback of findings method pertaining to the needs and preferences of the patient community. Aims: To investigate parents' understanding of the genomic research study they are participating in as well as their preferences regarding the feedback process and anticipated contributions of significant genetic findings generated by the NeuroDev study. This study further hopes to inform a tailored feedback policy reflecting the needs of this South African population. Research Design: A pragmatic qualitative approach was used by conducting 12 semi-structured interviews with 17 parents of children participating in the NeuroDev study. Purposive sampling was used, selecting retrospectively from patients recruited for the NeuroDev study in which findings of de novo, significant mutations are more likely expected. Interviews were conducted in English, in a private setting at Red Cross War Memorial Children's Hospital (RCWMCH), and were audio-recorded by the researcher; observations and field notes were documented. Generated data was analyzed using thematic analysis to generate themes and transcripts were imported into NVivo 12 to assist with managing and organizing the data for analysis. Ethical approval was been obtained from the University of Cape Town (UCT) (HREC 784/2018). Results: Empiric data collection ran from May to July 2019 and preliminary data was presented at the NeuroDev AGM and on a poster at the SASHG conference, RCWMCH research open day and UCT postgraduate research day. Findings were that the parents of the participants understood the study they were participating in as well as basic concepts of genetics, however, parental understanding over the cause of their child's condition remains a source of confusion when pertaining to their understanding of genetics being ‘passed down the family lineage' and how that integrates with de novo mutations. Furthermore, there is potential for it to impact on feelings of guilt. Parents have a need for information, discovering the cause of their child's condition and to be involved in the research process with full disclosure as events unfold. Altruism seems to be a major motivator for participating in genomics research but personal and family benefit also served to be a key driver in that research results could potentially provide awareness and information regarding their child's condition, the management thereof and recurrence risk in future. Participants in this study want pertinent research results which could offer closure, acceptance and relief, however, differences over the meaning of such results were observed between those whose child already had a diagnosis versus those whose child remained undiagnosed. Furthermore, receiving non-pertinent and negative result was still perceived to be meaningful for some. Further diversity was observed in parental preferences for the explanation of preliminary results. Discussion: Given that non-pertinent results still hold value for participants, consideration should be given as to more extensive ways of communicating this if such results are not to be returned since results are generally viewed as a point of access to information or relating to their child's condition. Diverse preferences regarding when and what participants want to know for results feedback needs to be addressed in order to facilitate a guidance framework for the delivery of genomic research results and can perhaps take the form of a tiered-consent model for feedback of incidental findings. As such, genetic counsellors may have a valuable role to play in facilitating participant satisfaction and bridging the gap between researchers and public expectations. Ethical considerations: Consent was taken before commencement of the study. There were no risks with regards to participating in this study and participants had the freedom to withdraw at any time and at their own discretion.